2016
DOI: 10.1002/adom.201500784
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Laser‐Induced Directional Recrystallization to Produce Single Crystal Silicon‐Core Optical Fibers with Low Loss

Abstract: Reduced losses in silicon‐core fibers are obtained using CO2 laser directional recrystallization of the core. Single crystals with aspect ratios up to 1500:1 are reported, limited by the scan range of the equipment. This processing technique holds promise for bringing crystalline silicon‐core fibers to a central role in nonlinear optics and signal processing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 23 publications
2
81
1
1
Order By: Relevance
“…The inset shows the deviation of the azimuthal angle of the diffraction spot on the detector as the fiber is translated, with variations less than ± 0.04 degrees from the average position. A single orientation was observed for the entire 2-3 mm annealed region of the fiber suggesting that larger single crystals could be produced [7,20] with a longer fiber. The annealed core material exhibited minimal strain and the clean, strong diffraction spot indicated that the crystal is of good quality.…”
Section: X-ray Diffractionmentioning
confidence: 87%
See 2 more Smart Citations
“…The inset shows the deviation of the azimuthal angle of the diffraction spot on the detector as the fiber is translated, with variations less than ± 0.04 degrees from the average position. A single orientation was observed for the entire 2-3 mm annealed region of the fiber suggesting that larger single crystals could be produced [7,20] with a longer fiber. The annealed core material exhibited minimal strain and the clean, strong diffraction spot indicated that the crystal is of good quality.…”
Section: X-ray Diffractionmentioning
confidence: 87%
“…The literature on Group IV semiconductor-core glass fibers is now significant [1][2][3][4][5], including processing improvements [6][7][8] and device demonstrations [9][10][11][12][13][14][15][16][17]. There are also reports on both SiGe alloy and II-VI core fibers [18][19][20][21][22][23], one including low temperature photoluminescence [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the as-drawn SCFs have revealed that material absorption due to impurities, scattering from grain boundaries and density fluctuations in the core are the major contributions of optical losses [4]. However, several approaches have been successfully employed to improve the material quality of the as-drawn SCFs, including thermal annealing, laser recrystallization [5], and tapering [6]. So far, propagation losses as low as 1dB/cm have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies are focused on post fiber drawing/deposition processes to decrease the transmission losses. 14,15 An earlier study reported measurement of the Raman shift in Ge-core fibers arising from a vibrational normal mode in Ge. 16 Here we report the first nonlinear off-resonance optical material response in the Ge core of as-drawn fibers.…”
Section: Introductionmentioning
confidence: 99%